2012
DOI: 10.1172/jci64906
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 orchestrates the bone-suppressing function of gut-derived serotonin

Abstract: Serotonin is a critical regulator of bone mass, fulfilling different functions depending on its site of synthesis. Brain-derived serotonin promotes osteoblast proliferation, whereas duodenal-derived serotonin suppresses it. To understand the molecular mechanisms of duodenal-derived serotonin action on osteoblasts, we explored its transcriptional mediation in mice. We found that the transcription factor FOXO1 is a crucial determinant of the effects of duodenum-derived serotonin on bone formation We identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 60 publications
2
55
1
Order By: Relevance
“…One explanation for this is that serotonin has an indirectly regulatory function on osteoblasts by acting on breast cancer. In contrast to a study by Kode et al (35), which showed no effect of serotonin on osteoclast differentiation, our studies in vitro found that circulating serotonin had a positive effect on osteoclast differentiation by acting on breast cancer cells. These striking findings suggest that depression decouples the remodeling process of the bone microenvironment by elevating the level of free serotonin, which results in metastatic bone loss by inhibiting bone formation and promoting bone resorption.…”
Section: Discussioncontrasting
confidence: 99%
“…One explanation for this is that serotonin has an indirectly regulatory function on osteoblasts by acting on breast cancer. In contrast to a study by Kode et al (35), which showed no effect of serotonin on osteoclast differentiation, our studies in vitro found that circulating serotonin had a positive effect on osteoclast differentiation by acting on breast cancer cells. These striking findings suggest that depression decouples the remodeling process of the bone microenvironment by elevating the level of free serotonin, which results in metastatic bone loss by inhibiting bone formation and promoting bone resorption.…”
Section: Discussioncontrasting
confidence: 99%
“…Serotonin was given at concentrations ranging from 25 to 100 mM, doses at which it affects the proliferation of cells expressing serotonin receptors. 37,40,41 Neither of these 2 treatments affected leukemic blast proliferation or survival (supplemental Figure 15). To confirm these observations in vivo, EL4 cells were treated with LP533401 or serotonin and subsequently implanted in mice to monitor leukemia engraftment, as commonly described.…”
Section: Increased Osteoblast Numbers Suppress Amlmentioning
confidence: 99%
“…To test this hypothesis, we treated mice with a compound, LP533401, that in rodents increases osteoblast numbers without affecting osteoclasts. [37][38][39][40] This effect involves inhibition of tryptophan hydroxylase-1 (Tph-1), an enzyme required in gut-derivedserotonin synthesis that suppresses osteoblast numbers.…”
Section: Increased Osteoblast Numbers Suppress Acute Lymphoblastic Lementioning
confidence: 99%
“…Moreover, in the peripheral system, serotonin also influences the physiological actions of FoxO, for example, serotonin enhances the proliferation of hepatocellular carcinoma cells through upregulation of FoxO3a (Liang et al, 2013) . Duodenum-derived serotonin is a critical regulator of bone mass during the process of bone formation, and importantly FoxO1 mediates this effect (Kode et al, 2012). High circulating serotonin levels prevent the association of FoxO1 with CREB, resulting in suppressed osteoblast proliferation (Kode et al, 2012).…”
Section: Antidepressants Regulate the Activities Of Foxosmentioning
confidence: 99%
“…Duodenum-derived serotonin is a critical regulator of bone mass during the process of bone formation, and importantly FoxO1 mediates this effect (Kode et al, 2012). High circulating serotonin levels prevent the association of FoxO1 with CREB, resulting in suppressed osteoblast proliferation (Kode et al, 2012). …”
Section: Antidepressants Regulate the Activities Of Foxosmentioning
confidence: 99%